Training on health communication and social media: European public health residents' perceptions. (13th November 2019) - de Nard, F; De Vita, E; Quattrone, F; Thomas, R; de la Torre, L
Abstract: Background: Theoretical knowledge about health communication (HC) and expertise in planning, implementation and evaluation of HC interventions are essential tools for Public Health (PH) specialists. In the social media (SM) era, specific abilities and digital communication skills are gaining importance. Objective: Our aim is to describe European PH residents' perceptions regarding their training in the HC field, with a focus on SM. We piloted a survey using Google Forms during the European Network of Medical Residents in PH (EuroNet MRPH) meeting in Turin, April 2019. We then spread the survey to other PH residents across Europe in July 2019. The survey consists of 25 questions (Likert scales from 1=strongly disagree to 5=strongly agree, or multiple-choices) divided in 5 thematic sections (HC theory, public speaking, traditional media based HC, SM based HC, HC impact evaluation). Questions aim to map HC topics covered in residency educational programs, learning methods, and the perceived importance of HC skills. Results: The study included 114 residents from 10 countries (37% Italy, 23% Portugal, 10% UK, 9% Spain, 8% France, 13% other). Participants perceived they receive the best training in the areas of public speaking, impact assessment and HC theory (median 3, IQR 2-4). Conversely, for traditional and SM based HC, training was perceived as unsatisfactory (median 2, IQR 1-4 and 1-3 respectively) with self-education as main learning method (51%). Public speaking and traditional HC were identified as the most important HC skills for PH specialists (median 5, IQR 5-5), while less importance was attributed to SM based HC (median 3, 5, IQR 3, 25-5). Conclusions: Despite SM are playing a crucial role in public HC, specific training seems to be scarce in this sample. Although residents perceive SM based HC skills as important, they consider them less important than other HC skills. Further analysis is needed in order to explore the perceived relevance of SM in PH residents training. Key messages: Training on health communication via social media is scarce among European public health residencies. Common training programs across European residencies in PH should address this educational need. European public health residents perceive social media based health communication skills as important, but not as important as traditional media based health communication skills.